Combination of sentinel lymph node mapping and uterine frozen section examination to reduce side‐specific lymphadenectomy rate in endometrial cancer: a Turkish Gynecologic Oncology Group study (TRSGO‐SLN‐002). Issue 7 (July 2020) - Altin, Duygu; Taşkın, Salih; Kahramanoglu, Ilker; Vatansever, Dogan; Tokgozoglu, Nedim; Karabük, Emine; Turan, Hasan; Takmaz, Özgüç; Naki, Mehmet Murat; Güngör, Mete; Köse, Mehmet Faruk; Ortac, Firat; et al.
ABSTRACT : Objective : This study aimed to find out whether side‐specific pelvic lymphadenectomy can be omitted without compromising diagnostic efficacy according to "reflex frozen section" analysis of the uterus in case of sentinel lymph node (SLN) mapping failure. Methods : Patients who underwent surgery for endometrial cancer with an SLN algorithm were stratified as low‐risk or high‐risk according to the uterine features on the final pathology reports. Two models for low‐risk patients were defined to omit side‐specific pelvic lymphadenectomy: strategy A included patients with endometrioid histology, grade 1‐2, and <50% myometrial invasion irrespective of the tumor diameter; strategy B included all factors of strategy A with the addition of tumor diameter ≤2 cm. Theoretical side‐specific pelvic lymphadenectomy rates were calculated for the two strategies, assuming side‐specific pelvic lymphadenectomy was omitted if low‐risk features were present on reflex uterine frozen examination, and compared with the standard National Comprehensive Cancer Network (NCCN) SLN algorithm. Results : 372 endometrial cancer patients were analyzed. 230 patients (61.8%) had endometrioid grade 1 or 2 tumors with <50% myometrial invasion (strategy A), and in 123 (53.4%) of these patients the tumor diameter was ≤2 cm (strategy B); 8 (3.5%) of the 230 cases had lymphatic metastasis. None of them were detected by side‐specific pelvic lymphadenectomy and metastases were limited to SLNs in 7 patients. At least one pelvic side was not mapped in 107 (28.8%) cases in the entire cohort, and all of these cases would require a side‐specific pelvic lymphadenectomy based on the NCCN SLN algorithm. This rate could have been significantly decreased to 11.8% and 19.4% by applying reflex frozen section examination of the uterus using strategy A and strategy B, respectively. Conclusion : Reflex frozen section examination of the uterus can be a feasible option to decide whether side‐specific pelvic lymphadenectomy is necessary for all the patients who failed to map with an SLN algorithm. If low‐risk factors are found on frozen section examination, side‐specific pelvic lymphadenectomy can be omitted without compromising diagnostic efficacy for lymphatic spread.